Ceramic Matrix Composites: Materials, Manufacturing and Engineering - Davim, J. Paulo; Jarzabek, Dariusz M; Zhang, Yongsheng; Aissa, Brahim; Bououdina, Mohamed; Dera, Wojciech; Fan, Hengzhong; Fang, Yuan; Fantozzi, Gilbert; Ferreira, José Maria (Advanced Composites, 2016)
Composite materials are engineered materials, made from two or more constituents with significantly different physical or chemical properties which remain separate on a macroscopic level within the finished structure. Due to their special mechanical and physical properties they have the potential to replace conventional materials.